A novel PTS based PAPR reduction scheme for FBMC-OQAM system without extra bits transmission of SI - Merah, Hocine; Merrad, Yacine; Habaebi, Mohamed Hadi; Mesri, Mokhtaria (Taylor & Francis & Informa UK Limited, trading as Taylor & Francis Group, 2020)
In this paper, a Novel Partial Transmit Sequence-based scheme is proposed, namely (N-PTS). The aim is to solve the major hindrance of high Peak to Average Power Ratio (PAPR); as well as to combat the overlapping structure issue affecting Filter Bank Multicarrier system based on the Offset Quadrature Amplitude Modulation (FBMC-OQAM). On that note, computational complexity is also reduced. The proposed scheme uses FBMC-OQAM signal in the frequency domain. To this end, the lowest PAPR value is calculated from data located in a Storage Device (SD). Accordingly, it is properly identified through its location referred to as ’Row’ which consists of the Side Information (SI) to recover the original signal at the receiver. As a result, a substantial reduction in PAPR and computational complexity are achieved. Finally, it is found necessary to mention that SI is claimed not to require extra bits to be transmitted, using phase offset with Minimum Euclidian Distance (MED) criterion, while the Bit Error Rate (BER) performance remains very satisfactory.